Applying the ecosystem approach to the Sundarbans of Bangladesh: Possibilities and challenges. Issue 2 (31st January 2018) - Alam, Shawkat; Mohammad, Sheikh Noor
Abstract : This article considers the relevance of the ecosystem approach as a suitable means of providing for the conservation and sustainable development of the endangered Sundarbans mangrove forests of Bangladesh. Commencing with the genesis of the ecosystem approach in international law and its incorporation in the Convention on Biological Diversity, the article considers its principles in the approach to the regulation, monitoring and management of the Sundarbans. It demonstrates that there is scope for key aspects of the ecosystem approach to be incorporated into the management regime for the Sundarbans. The accommodation of the interests of forest‐dependent communities and the focus on adaptive management are among the aspects of the ecosystem approach that benefit sustainable management for the region. However, successful incorporation of its principles will only be possible if the relevant legislative framework is extensively amended, efforts are made to build the awareness and capacity of forest users to manage the resources on which they rely, and financial support is increased to facilitate the transition to an ecosystem approach‐based management of the Sundarbans.